The internet as a new civic form - Jouët, Josiane (Javnost (Ljubljana), 2009)
The article argues that, beyond the boundaries of activists and concerned citizens, the massive appropriation of the Internet techniques of self-publication and the social modes of interactions on the web, lead to the extension of the public sphere to the rank-and-fi le. It takes the position that civic culture is not homogeneous and that it is shaped by diff erent social practices that we examine through three sets of digital public spheres. First, the rise of 'free speech' in professional journalistic practices on media websites expands to readersć voices (in forums, online surveys, readers' comments), while citizens' engagement in amateur grassroots journalism challenges both the professional practices and the ethics of journalism. Second, the lively political blogosphere demonstrates how personal opinions on public matters find their legitimacy in the interactive dialogue in and across networks and lead to the emergence of rank-and-file opinion leaders, while also presenting various pitfalls, such as the redundancy of a limited number of viewpoints. Third, the social and leisurely Internet usage of ordinary citizens leads them to confront political and public issues in a casual and random manner, which in turn leads them to discuss these matters occasionally in online or face-to-face settings. This trend is reinforced by the innovative creation of user-generated content, mixing text, sound, and video formats that are widely circulated on the web. The rise of new forms of political and social critique on the Internet and the sharing of common experiences in the electronic space results in novel mean of public engagement and contributes to the shaping of a new civic and social form.
Keywords: javnost; komuniciranje; communication; sociologija komunikacij; komunikacijska tehnologija; internet (računalniško omrežje); France; Francija